MENINGKATKAN KUALITAS PELAYANAN BISNIS MAKANAN PEMPEK DI KOTA PALEMBANG - Muhammad Yusuf (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2015)
Pempek is a typical food Palembang and very popular. The much number of business competitions in the field of pempek requires the businesses need to improve the quality of service to become win the competition. This study aims to determine the effect of the dimensions of service quality on customer satisfaction pempek store in Palembang. This research was conducted at the store Pempek "CANDY" and store Pempek "SENTOSA". The both object of the study to be representative of the research object pempek food business. The focus of this research is to determine how much influence the quality of services consisting of the dimensions of tangible, reliability, responsiveness, assurance, and empathy for customer satisfaction. The indicators of variable tangible are facilities, equipment, decoration of the place and neatness employee clothing. The indicators of variable reliability are accuracy, timeliness, the same service and the nature of the employee sympathy to the consumer. The indicators variable responsiveness are fast service, accurate and clear information. The indicators of variable assurance are knowledge of employees about the products and the ability to foster a sense of consumer confidence. Lastly, the indicators of variable empathy are to know the needs and taste of concern to consumers. The sample of this study is 60 respondents. The technique of determining the sample was accidental sampling. The research data obtained by distributing questionnaires to consumers. Based on the results of this study note that the variables that significantly influence to customer satisfaction for business pempek in Palembang is variable tangible, responsiveness and empathy. There are two variables not significant, namely reliability and assurance variable. The results of this study recommend that to improve the quality of service to consumers conducted by pempek store in Palembang necessary improvements in terms of accuracy, timeliness, same service, sympathy for the consumer, employee knowledge about the products and growing consumer confidence.